Answer:
(
, -
)
Explanation:
8x + 4y = 7 → (1)
6x - 8y = 41 → (2)
multiplying (1) by 2 and adding to (2) will eliminate y
16x + 8y = 14 → (3)
add (2) and (3) term by term to eliminate y
22x + 0 = 55
22x = 55 ( divide both sides by 22 )
x =
=
![(5)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/20of65aiaodmwt70qegyyu14z3ype8cwhf.png)
substitute this value into either of the 2 equations and solve for y
substituting into (1)
8(
) + 4y = 7
20 + 4y = 7 ( subtract 20 from both sides )
4y = - 13 ( divide both sides by 4 )
y = -
![(13)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/r2wedw1p74iyz6z4b5pzh2ncag6nz1757a.png)
solution is (
, -
)